Analisa Pengaruh E-Arsip Sebagai Pengolahan Data Terhadap Kinerja Pegawai (Kasus: KKP Wilayah Kerja Pelabuhan Sungai Duku Pekanbaru) - Bayu Febriadi; Pandu Pratama Putra; Febrizal Alfarasy Syam; Didik Siswanto (LPPM STIKOM Tunas Bangsa, 2023)
Class II Pekanbaru Port Health Office is a Technical Implementation Unit (UPT) under the Ministry of Health that is under the responsibility of the Director General of Disease Control and Environmental Health (Dirjen PP and PL). Based on Ministry of Health Regulation No. 2348 of 2011, Class II Pekanbaru Port Health Office has seven work areas, consisting of six work areas, such as the Kampung Dalam Work Area, Selat Panjang Sea Port Work Area, Buatan River Port Work Area, Siak Port Work Area, Tanjung Buton Sea Port Work Area, and Pekanbaru Duku River Port Work Area. However, data processing in the Pekanbaru Duku River Port work area has not been well-integrated with the head office, causing Class II Pekanbaru Port Health Office employees to face difficulties in data collection and presentation of information from daily activities and data archiving, such as ship surveillance, public health surveillance, and disease data surveillance. This also affects the performance of employees and the Class II Pekanbaru Port Health Office. It is hoped that the use of e-Archive as an information technology-based data and document management system can improve the performance of Class II Pekanbaru Port Health Office employees in presenting data and reporting documents.